How does loneliness affect satisfaction with life? What is the role of the perception of God in this interaction? - Kaya, Feridun; Yazıcı Çelebi, Gülin (Frontiers in Psychology, 2025)
IntroductionThis study examined the role of loneliness and the perception of God in affecting the satisfaction with life of Muslim individuals living alone in Turkey during the COVID-19 pandemic. Additionally, the study explored the regulatory role of the perception of God in the relationship between individuals’ loneliness and satisfaction with life.MethodsThe research is a cross-sectional study that evaluates individuals’ loneliness, satisfaction with life, and perception of God. The study group consists of 378 individuals living alone in Turkey. Among the participants, 196 are women (51.9%) and 182 are men (48.1%). The UCLA loneliness scale, the satisfaction with life scale, the perception of God scale, and a personal information form were used as data collection tools in the study.ResultsThe examination of research findings indicated that the variables of loneliness, perception of God, and the interaction between loneliness and the perception of God explained 28% of the variance in individuals’ satisfaction with life. We determined that satisfaction with life was affected significantly and positively by the perception of God (β = 0.28, p < 0.001) and significantly and negatively by loneliness (β = −0.38, p < 0.001). The interactional effect of the variables of loneliness and perception of God on satisfaction with life was also found to be significant (β = −0.10, p = 0.023). When we examined the details of the regulatory effect, we found that the effect of loneliness on satisfaction with life decreased even more in cases where the perception of God was high.DiscussionThe research findings suggest that loneliness decreases life satisfaction, while positive self-image mitigates this effect. It can be stated that using belief-sensitive therapeutic approaches in the therapeutic process could contribute to alleviating the negative effects of loneliness.